MAKNA TUTURAN DALAM PENYELESAIAN PELANGGARAN ADAT MAMBOLOSUAKO MASYARAKAT TOLAKI - Ino, La (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2011)
This article studies about one of cultural products at Tolaki ethnic in South-East Sulawesi Province. The cultural product is mombolusuako.Â Mombolosuako is a tradition in Tolaki society, in which someone, a man, did a breach of custom that usually happen when the relationship between the girl and the young man is not agreed by the parents and when the girl and the man have different social status. Because it is a breach of custom, there should be a solution according to the custom. In solving this problem (mombolasuako), the custom provides two steps rembinggare and mesokei. The method used in research is descriptive qualitative method. The subject of research is the informants mastering in uttering the solution of the breach of custom (Mombolasuako) in Tolaki society in Lambuya subdistrict. This study is done by using semantic and pragmatic approach. In solving the mombolasuako the people use the language with particular characteristics that is different from their daily language. The language emphasizes beauty especially in its use of language speech and metaphors.Â The rembinggare is meaningful for the man family, as to show his intention to solve the problem, and it is meaningful for the family of the girl as the solution of the problem so that they will be avoided from shame.Â In the process of mesokei there is a negotiation and settlement among two families to get the best solution for both of them.